?COCONUT PALM (COCOS NUCIFERA) HUSK AS A POTENTIAL ADSORBENT FOR LEAD, CADMIUM AND ZINC IONS IN INDUSTRIAL WASTE EFFLUENTS (Biological Sciences - PJSIR, 1997)
Sorption oflead, cadmium and zinc ions from aqueous effluents by coconut (Cocosnucifera) husk is reported. Results show that more than eighty percent removal could be achieved in the column experiments. The sorption of the metal ions vary markedly with the type of metal ion and follows the order lead> cadmium> zinc ions and its initial concentration. Its use for binding lead, cadmium and zinc ions in mining waste effluents is recommended.